Perspectives on the role of nutrition in influencing academy soccer player development and performance: A qualitative case study of key stakeholders from an English category one soccer academy - Carney, D: J.; Hannon, M. P.; Murphy, R. C.; Close, G. L.; Morton, J. P. (Journal of Sports Sciences, 2024)
This study aimed to explore player and stakeholder perceptions of the role of nutrition in influencing the development of male academy soccer players. Semi-structured interviews (28 ± 13 mins in length) were conducted with 31 participants from an English category one academy, including players (Youth Development Phase, YDP: n = 6; Professional Development Phase, PDP: n = 4), parents/guardians (n = 10), coaches (n = 3), sport scientists (n = 3), physiotherapists (n = 3), and catering (n = 2). Via reflexive thematic analysis, data demonstrate an apparent lack of understanding and awareness on the role of nutrition in influencing player development, especially in relation to growth, maturation and reducing injury risk. Players highlighted the influence of their parents on their dietary behaviours, whilst parents also called for education to better support their sons. Notably, players and stakeholders perceived that the daily schedule of an academy soccer player presents as "too busy to eat", especially in relation to before school, and before and after training. The results demonstrate the necessity for the co-creation of player and stakeholder specific nutrition education programmes as an initial step towards positively impacting the nutrition culture associated with the academy soccer environment.